2019
DOI: 10.1049/iet-epa.2019.0035
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an STSMO‐based estimator for power control of rotor‐tied DFIG systems

Abstract: In this study, a sensorless vector control strategy of a rotor-tied doubly fed induction generator (RDFIG) system based on the association of the phase-locked loop (PLL) estimator and the super-twisting sliding mode observer (STSMO) is proposed and analysed. The proposed sensorless control strategy utilises the stator current and the back-electromotive force (EMF) as state variables. The advantage of the proposed sensorless control strategy is that the estimation process is conducted before the machine is conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…According to the above, the output reference of the rotor voltage is expressed as [14,35]: The expression of the super twisting output laws does not depend on the value of ( S, Ṡ ), but only of their signs. Fig.…”
Section: High Order Sliding Mode Control Of Dfigmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the above, the output reference of the rotor voltage is expressed as [14,35]: The expression of the super twisting output laws does not depend on the value of ( S, Ṡ ), but only of their signs. Fig.…”
Section: High Order Sliding Mode Control Of Dfigmentioning
confidence: 99%
“…The high order sliding mode approach presents another typical effective solution to eliminate the chattering problem, by keeping the same first-order sliding mode behaviors, especially the convergence properties and the control accuracy [13]. The super-twisting algorithm is an exception in a class of second-order sliding mode control, it can reduce chattering problems due to the discontinuity of the control signal [14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the saliency‐based estimation methods are mostly suitable for standstill and start‐up operating conditions. The model‐based estimation techniques are used to estimate the rotor speed/position based on the machine model at the fundamental frequency and they are mostly used for medium‐speed and high‐speed applications [10–32]. The model‐based estimation techniques are generally grouped into two categories: the open loop calculations and closed loop observers.…”
Section: Introductionmentioning
confidence: 99%
“…Another SMO‐based estimator, the super twisting sliding mode observer (STSMO), is proposed for the sensor‐less control of the RDFIG in ref. [31], whereby it was shown that the use of the super twisting algorithm (STA) improves the performance of the proposed position/speed estimator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation